Remainder with Threshold Substitution Data Hiding Scheme: Counterexamples and Modification - Chefranov, Alexander; Oz, Gurcu (IEEE-Inst Electrical Electronics Engineers Inc, 2023)
A well-known data hiding scheme, Remainder with Threshold substitution (RT), is analyzed. RT uses a threshold value, T, and two moduli numbers, m(u), and m(l), m(l)
Keywords: Data hiding scheme; Remainder with Threshold substitution; Cover Image; Pixel; Secret Embedding; Secret Extraction